Estrategias didácticas para el desarrollo de la lectura comprensiva en los niños de 3ero. “a” de la unidad educativa combatientes de Tapi n°.6 “Comil”, provincia de Chimborazo, cantón Riobamba, año lectivo 2015-2016 - Gadvay Moyota, Mariela Fernanda (2016)
The present research was developed by the aim to motivate the students on the importance of the didactic strategies for the development of the comprehensive reading, the same one that appears under five chapters, in which follows a logical and organized into a hierarchy order. Inside the referential frame the problem to investigating, its causes and consequences, its general aim that is determine which are the strategies that develop the comprehensive reading in addition is supported of its specific aims and finally the reason appears and the work is justifiable. Later we have to the theoretical frame giving emphasis in direction of both variables with their respective sub subjects therefore in it there are announced the didactic strategies that help to the development of the comprehensive reading. In the methodological frame there developed the scientific method. - The one who gives bibliographical bases on authors' knowledge; inductive method. – Because report of particular facts to come to the general of the investigation; deductive. - Because it goes from the general thing to the particular of the facts. The kind of investigation was documentary and of field, because it compile information of leaflets, texts and Internet for the general interpretation on the importance about didactic strategies that appeared at Combatientes de Tapi N° 6 “COMIL” high school; and applied type because it happens in the reality of the facts for accomplishment of the investigated project, considering the population and sample that we worked it. The observation was the technique and the instrument was the card of observation. The results allowed to realize the analysis and interpretation of the information finally to establish the conclusions and recommendations where the development of reading comprehension in students is emphasized.